From Nature to Fabrication: Biomimetic Design Principles for the Production of Complex Spatial Structures. Issue 1 (March 2013) - Magna, Riccardo La; Gabler, Markus; Reichert, Steffen; Schwinn, Tobias; Waimer, Frédéric; Menges, Achim; Knippers, Jan
In the current paper the authors present a biomimetic design methodology based on the analysis of the Echinoids (sea urchin and sand dollar) and the transfer of its structural morphology into a built full-scale prototype. In the first part, an efficient wood jointing technique for planar sheets of wood through novel robotically fabricated finger-joints is introduced together with an investigation of the biological principles of plate structures and their mechanical features. Subsequently, the identified structural principles are translated and verified with the aid of a Finite Element Model, as well as a generative design system incorporating the rules and constraints of fabrication. The paper concludes with the presentation of a full-scale biomimetic prototype which integrates these morphological and mechanical principles to achieve an efficient and high-performing lightweight structure.